Improved injury management at an Australian aluminium smelter - Viljoen, D.; Guest, M.; Boggess, M.; Duke, Janine (IOS Press, 2010)
Objective: This longitudinal study sought to determine the effectiveness of interventions to improve injury management in an industrial setting. Participants: Study participants were workers from three production departments of a large aluminium smelter. Methods: The interventions introduced were to encourage active participation in rehabilitation procedures by injured workers, improve communication with all stakeholders, identify and manage psychosocial issues, and focus the workforce on occupational health and safety matters. Linear regression modelling was used to determine the effectiveness of the interventions using data collected for fourteen months before and fifteen months after the introduction of interventions. Outcomes compared were the number of injuries, number of persons on restricted duty, and lost hours per month. Results: Modelling showed the intervention significantly reduced the number of injuries in the potrooms (from 14 to 6 per month). The number of persons on restricted duties was reduced in all departments (potrooms: from 12 to 7 persons per month, cast house: 3 to 1 person per month, carbon plant: 3 to 1 person per month). Lost hours were significantly reduced in the potrooms (from 244 to 61 hours per month). Conclusion: These findings demonstrate the effectiveness of the revised injury management process introduced.